2011
DOI: 10.1038/sc.2011.112
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute overdose or withdrawal state in intrathecal baclofen therapy

Abstract: Study design: Individuals who are treated with intrathecal Baclofen (ITB) pump delivery system for intractable spasticity can suffer from severe morbidity as a result of acute overdose or withdrawal of ITB, which can also be life threatening. Current literature has a number of single case studies with different approaches to the management in such states. Objectives: The aim of this article is to consolidate available evidence and develop treatment pathways for acute ITB overdose and withdrawal states. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…3,10,14,20,21,25,32,47 Baclofen withdrawal symptoms can begin within the first 3 days after slowing or stopping the medication, whether orally or intrathecally. 10,29,38,39,46,47 These symptoms are likely caused by the removal of the inhibitory tone on the GABA B receptors. 10,38,46 Catheter-related complications are the most common type of complication associated with intrathecal baclofen pumps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,10,14,20,21,25,32,47 Baclofen withdrawal symptoms can begin within the first 3 days after slowing or stopping the medication, whether orally or intrathecally. 10,29,38,39,46,47 These symptoms are likely caused by the removal of the inhibitory tone on the GABA B receptors. 10,38,46 Catheter-related complications are the most common type of complication associated with intrathecal baclofen pumps.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,10,11,14,[19][20][21][22]25,31,32,37,40,47 Watve et al observed that intrathecal baclofen withdrawal is frequently due to catheter malfunction. 46 Baclofen withdrawal can be characterized by reflex spasticity, seizures, central nervous system depression, and hyperthermia, which may progress to disseminated intravascular coagulation and organ failure if left untreated. 3,10,14,20,21,25,32,47 Baclofen withdrawal symptoms can begin within the first 3 days after slowing or stopping the medication, whether orally or intrathecally.…”
Section: Discussionmentioning
confidence: 99%
“…In the opinion of the authors of the current study, however, acute psychosis after baclofen poisoning does not depend on its dose, and it is rather a 'withdrawal' symptom. Therefore, chronic baclofen therapy, for example, should not be discontinued abruptly, as rapid cessation may lead to development of severe withdrawal symptoms [1,17,18]. Treatment of baclofen intoxication is mainly supportive.…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, the complications are the result of a problem with the catheter. 1,3,[9][10][11] Intrinsic pump malfunction appears to be a rare complication; there is only 1 reported case in the current literature. 10 In this paper, we present the case of a 10-year-old boy who progressed to acute baclofen overdose on 2 separate occasions after baclofen pump refill by 2 different individuals.…”
mentioning
confidence: 90%